Strategy to Combine Clauses In Waijewa Dialect A Sumbanese Language - Kasni, Ni Wayan (e-Journal of Linguistics, 2012)
Clause is defined as a grammatical unit consisting of the elements of subject (S) and predicate (P), both with object (O) and adverbial (A), and has the capability of being a sentence. Clauses can be categorized based on (i) the core arguments, (ii)  the presence or absence of negative words in predicate, (iii) the categories of words or phrases that occupy predicate function, (iv)  its capacity of being a sentence, (v)  their functions in sentences. A clause can be combined in two ways, first using coordinate conjunction forming a coordinate construction, and second using subordinate conjunction forming a subordinate construction. This research attempted to analyze the strategy of combining clauses in Waijewa Dialect; a Sumbanese language. This research applied qualitative method in which the written data were collected from three key informants and four supporting informants from each district in Waijewa using four techniques namely; (1) observation, (2) structure-based interview, (3) documentation, and (4) triangulation. The collected data were analyzed using distributional method. The theory used to analyze the data was the language typology theory proposed by Dixon (1994) and 2010) and Comrie (1983). The result showed that in Waijewa dialect clauses could be divided into two; namely, the clauses having verbal predicates and the ones having nonverbal predicates. Waijewa dialect has clitic pronouns marking the arguments of the verbs. They showed nominative, accusative, and genitive cases. The coordinate constructions in BSDW could be categorized into two forms such as:  (1) syndetic (construction marked by conjunction) and (2) asyndetic (without conjunction marker). The forms of subordinate clause in subordinate construction were divided into three; namely, (1) relative clause, (2) complementation clause, and (3) adjunct clause. Arguments A and S were relativized by gapping and attaching the prefix {a-} to the V and the relativization of the arguments O, E, locative, and instrument was done by gapping and attaching prefix {pa-} to the V. The complementation clause could be combined using either the conjunction ba ‘that’ or without the conjunction ba , verb serialization, relative clause construction, purposive linking with the conjunction {ka} ‘for’ or without the conjunction ka . The adjunct clause could be combined using either conjunction or without conjunction.
Keywords: : clitic, nominative, accusative, genitive, syndetic, asyndetic.